Difficulties and Cracking the Judicial Recognition of “Aggravating Circumstances” in Internet Defamation Crimes - Fu, Ruifang (International Journal of Social Sciences and Public Administration, 2025)
The judicial determination of “aggravating circumstances” in online defamation is crucial, but faces many difficulties. The quantitative standard is irrational to criminalize the behavior of others, and it is difficult to reflect the effect of deeper dissemination; the assessment of the harmful consequences has the problems of vague definition of the scope and degree, and complicated determination of causality. The path to solving the problem lies in clarifying the substantive judgment standard of “quantity”, improving the diversified determination standard, comprehensively considering the degree of evil of defamation and the degree of infringement on the victim’s reputation, and constructing a comprehensive assessment system by drawing on foreign experience. In-depth study of these issues is of great significance to the improvement of judicial practice and the protection of the legitimate rights and interests of citizens.